2018
DOI: 10.3390/s18113786
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Five Different Soil Moisture Sensors under Irrigated Field Conditions in Oklahoma

Abstract: Meeting the ever-increasing global food, feed, and fiber demands while conserving the quantity and quality of limited agricultural water resources and maintaining the sustainability of irrigated agriculture requires optimizing irrigation management using advanced technologies such as soil moisture sensors. In this study, the performance of five different soil moisture sensors was evaluated for their accuracy in two irrigated cropping systems, one each in central and southwest Oklahoma, with variable levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
2
24
1
2
Order By: Relevance
“…The GS1 sensor also had low RMSE (0.026 m 3 m −3 ) ( Table 3). This value was smaller than the RMSE value of 0.048 reported by Datta et al [6] for the GS1 in a fine sandy loam soil. These authors reported that TDR315, CS655, and GS1 sensors performed better in a soil with lower salinity and lower clay content.…”
Section: Manufacturercontrasting
confidence: 69%
See 2 more Smart Citations
“…The GS1 sensor also had low RMSE (0.026 m 3 m −3 ) ( Table 3). This value was smaller than the RMSE value of 0.048 reported by Datta et al [6] for the GS1 in a fine sandy loam soil. These authors reported that TDR315, CS655, and GS1 sensors performed better in a soil with lower salinity and lower clay content.…”
Section: Manufacturercontrasting
confidence: 69%
“…Many researchers have also reported overestimation of θv by the CS655 sensor [56][57][58]. Similar results from Datta et al [6] showed that all sensors (TDR315, CS655, and GS1) overestimated θv in a low clay content soil located in central Oklahoma. Adeyemi et al [52] found that TDR315 and GS1 underestimated θv in sandy loam soil.…”
Section: Manufacturersupporting
confidence: 58%
See 1 more Smart Citation
“…Data from GS-1 soil moisture sensors in situ at the location of the soil sampling sites were collected for an uncertainty analysis for use in irrigation scheduling. Previously, Datta et al (2018) suggested that GS-1 sensors presented acceptable accuracies for managing irrigation at sites with low salinity and low clay content based on the reported root mean square errors. In the current study, the capacitance-based GS-1 sensors were installed and monitored for the 2018 growing season at depths of 0.15, 0.46, and 0.76 m. The temporal trends ( fig.…”
Section: Implications For Irrigation Managementmentioning
confidence: 99%
“…The performance of EM soil water sensors under various soil conditions has been investigated extensively (Geesing et al, 2004;Mittelbach et al, 2012;Singh et al, 2018;Varble and Chávez, 2011;Vaz et al, 2013), and some studies have proposed correcting for non-water influences on  v by developing soil-specific calibrations. For soil moisture sensors based on capacitance and frequency domain technology, the sensor response over a large  v range has been captured in the laboratory (Adeyemi et al, 2016;Goswami et al, 2019;Ojo et al, 2015;Provenzano et al, 2016;Santhosh et al, 2017) and in the field (Datta et al, 2018;Huang et al, 2017;Lea-Cox et al, 2018;Ojo et al, 2014;Rudnick et al, 2015;Sui, 2017).…”
mentioning
confidence: 99%